2018
DOI: 10.1308/rcsann.2017.0147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mechanism on the management and outcome of penetrating colonic trauma

Abstract: Introduction In light of continuing controversy surrounding the management of penetrating colonic injuries, we set out to compare the outcome of penetrating colonic trauma according to whether the mechanism of injury was a stab wound or a gunshot wound. Methods Our trauma registry was interrogated for the 5-year period from January 2012 to December 2016. All patients over the age of 18 years with penetrating trauma (stab or gunshot) and with intraoperatively proven colonic injury were reviewed. Details of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
7
4
0
1
Order By: Relevance
“…An additional six patients developed anastomotic leakage. These results are comparable to literature with anastomotic leakage rates of 2-15% following trauma [35][36][37][38][39]. There was a relatively high number of patients who needed a laparotomy several days after the initial trauma in whom a primary anastomosis was performed (2/14 anastomoses > 48 h; 14.2%).…”
Section: Discussionsupporting
confidence: 84%
“…An additional six patients developed anastomotic leakage. These results are comparable to literature with anastomotic leakage rates of 2-15% following trauma [35][36][37][38][39]. There was a relatively high number of patients who needed a laparotomy several days after the initial trauma in whom a primary anastomosis was performed (2/14 anastomoses > 48 h; 14.2%).…”
Section: Discussionsupporting
confidence: 84%
“…Similar to other reports, the left colon part (i.e. splenic colon exure, descending and sigmoid colon) and middle colon (ascending and descending colon) were frequently injured as compared to other sites (1,10,(20)(21)(22)(23). The importance to note that colon part injury is related to a higher risk of fecal diversion.…”
Section: Discussionsupporting
confidence: 80%
“…Unlike other research carried out in this area, we showed multiple injuries to the colon in 58% of patients, which is higher compared to other combat cohorts. For example, Oosthuizen et al showed 12% and Steele et al 15% of multiple injuries in patients diagnosed with more than one injury to the colon in the study of non-combat trauma (20,22). Cardi et al demonstrated multiple segment injuries in both large and small bowel in 21.3% of the patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…Hollow viscus injuries represent a significant portion of overall lesions sustained during penetrating trauma [1][2][3][4][5] . Currently, isolated small or large bowel injuries are commonly managed via primary anastomosis in patients undergoing definitive laparotomy or deferred anastomosis in patients requiring Damage Control Surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Las lesiones del intestino y colon representan una alta proporción de todas las heridas ocasionadas por trauma penetrante 1 - 5 . Actualmente, las lesiones aisladas de intestino delgado o colon se manejan con anastomosis primaria o diferida, ya sea por medio de una laparotomía definitiva o una cirugía de control de daños, respectivamente.…”
Section: Introductionunclassified